Doing Philosophy Effectively: Student Learning in Classroom Teaching - Kienstra, Natascha (PLoS One, 2015)
An important aim of teaching philosophy in Dutch secondary schools is to learn about philosophy (i.e., the great philosophers) by doing philosophy. We examined doing philosophy and focused specifically on the relationship between student learning activities and teacher behavior; in doing so, a qualitative cross-case analysis of eight philosophy lessons was performed. The effectiveness of doing philosophy was operationalized into five learning activities comprising rationalizing, analyzing, testing, producing criticism, and reflecting, and scored by means of qualitative graphical time registration. Using CA we find a quantitative one-dimensional scale for the lessons that contrasts lessons that are more and less effective in terms of learning and teaching. A relationship was found between teaching by teachers and doing philosophy by students. In particular we found students to produce a higher level of doing philosophy with teachers who chose to organize a philosophical discussion with shared guidance by the teacher together with the students.